The Green Deal: A Call for Changed Lifestyle - Inman, Samuel (Maine Policy Review, 2007)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. This year students were asked for a comprehensive national energy policy, addressing the topic from multiple perspectives and surveying the economic, environmental, political social and historical considerations that must go into any viable long-term solutions. Featured here is Samuel S. Inman’s thoughtful and well-articulated 2007 first place prize-winning essay.